Efektivitas Kegiatan Bernyanyi dalam Mengembangkan Kosakata Bahasa Inggris Siswa Kelas I SDN 039 Air Terbit Kabupaten Kampar - Latifah Salsabila Anisa Udiyani; Radhiyatul Fithri; Salma Salma (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
English is an international language, some countries make English a second language after their native language. Learning English from an early age is certainly a good thing, because it cannot be denied that learning English is important and beneficial for a person’s future. In the initial stages of learning English, what is very important to learn first is learning vocabulary, because vocabulary will help someone to learn someone to learn English at the next step and help someone be able to cummunicate using English well. SDN 039 Air Terbit applies singing activities in carrying out English vocabulary learning, singing activities can help students develop and memorize English vocabulary easily, especially for class 1 students, this activity will certainly make class 1 students more antusiastic in memorize English vocabulary. The purpose of this research is : (1) to find out how singing activities are implemented in learning english vocabulary for class 1 students at SDN 039 Air Terbit, (2) to determine the effectiveness of singing activities in developing the vocabulary of class 1 students SDN 039 Air Terbit. This research method is qualitative research, the data collection techniques used are through observation, interviews and documentation.